Associations between the erythropoiesis-stimulating agent resistance index and the geriatric nutritional risk index of maintenance hemodialysis patients and increased mortality. Issue 1 (December 2015) - Okazaki, Masayuki; Komatsu, Mizuki; Shiohira, Shunji; Kataoka, Hiroshi; Tsuchiya, Ken; Kawaguchi, Hiroshi; Nitta, Kosaku
Abstract Background There may be an association between the responsiveness to erythropoiesis-stimulating agent (ESA) and the nutritional status on mortality of maintenance hemodialysis (MHD) patients. Therefore, we assessed the associations of geriatric nutritional risk index (GNRI) and ESA resistance index (ERI) in mortality in MHD patients. Methods A total of 298 MHD patients were enrolled. Unadjusted and adjusted Cox regression analyses for all-cause mortality were performed. Odds ratios were estimated using a logistic regression model for the association between the GNRI and ERI and mortality, adjusting for potential confounders. Results During the follow-up period of 34.6 ± 6.1 months, 51 died with 31 cardiovascular deaths. Receiver operating curve analyses indicated the cutoff values of GNRI and ERI for mortality were 94.9 and 13.5, respectively. When subjects were stratified by ERI and GNRI values into four groups, those who had low GNRI and high ERI were associated with the highest risk of mortality among the four groups (log-rankp < 0.001). Conclusions High ERI and low GNRI were associated with an increased risk of all-cause mortality.